Business Sustainability : Its Definitions, Reporting Constructs, Integration into Corporate Strategy and Economics Consequences - A Malaysian Perspective - Lew, Stephen Joo Wei; Hamdi, Aishath Asna (2015)
There has been an increasing trend in sustainability reporting worldwide over the last decade. ASEAN countries have also been increasingly involved in sustainability reporting with Malaysia leading the way. Bursa Malaysia has been advocating business sustainability and this can be seen by its introduction of a CSR framework in 2006 and its further repositioning to a business sustainability framework in 2010. While firms are realising the importance of operating in a sustainable way, relatively little is known about the nature, extent, and effectiveness of business sustainability and its strategic importance. Furthermore, firms are at a different level of understanding when it comes to applying and integrating business sustainability initiatives (BSI). The purpose of this study is to explore the concept of business sustainability, determine the constructs of BSI and examine which of these are embraced by the Malaysian PLCs and communicated to their stakeholders, observe how Malaysian public listed firms (PLCs) have integrated sustainability into their strategic management process, and derive the economic consequences and value BSI. In order to better understand the concept of business sustainability and how it has evolved as well as its constructs, both contemporary and conventional literatures as well as industry practitioner views were considered to derive a Comprehensive perspective. In addition, further study was performed to understand how strategic business sustainability could be undertaken. With this in view, the annual and sustainability reports of the top 100 Bursa Malaysia firms were analysed by means of content analysis to quantify the disclosures of BSI. This in turn allows the analyses of the types of disclosures as well as enables the classification of both High and Low BSI firms which would enable the analyses of the economic consequences of BSI through the testing of key financial indicators. This study as part of its findings has observed that Malaysian firms do indeed have varying levels of understanding with regards to business sustainability. This can be seen in both the level of strategic sustainability integration within Malaysian firms as well as the varying levels of disclosures between the business sustainability dimensions. It can be seen that larger firms do outperform smaller firms with regards to the implementation of business sustainability, and these points are consistent with literature. In addition, some observations regarding the economic consequences of business sustainability to Malaysian firms were also made. In terms of financial performance, the results were inconclusive. Nonetheless, it was observed that with increased BSI, Malaysian firms displayed increased Economic Value Added (EVA) figures, and Price to Equity Ratio (PER) levels. The study therefore concludes that while Malaysian firms are beginning embrace business sustainability, it is still in the nascent stages of development and while some degrees of economic benefits are observed, the results are still inconclusive at this stage.